A Modified UNIFAC Model for Polymer Solutions - Cheng, Zhenfeng; Li, Changyou (Asian Journal of Chemistry, 2012)
For not considering the effect of free volume, the predictive results of the UNIFAC model in polymer solution systems are not acceptable. To improve the predictive accuracy, a free-volume term derived from the van der Waals partition function is added into the UNIFAC model, experimental data of 19 polymer solution systems are used to test the modified model, which is compared with the UNIFAC model, the UNIFAC-FV model and the Entropic-FV-1.2 model, and the results showed that the modified model is mostly better than other models. Furthermore, the model is valid for the whole range of polymer concentration (from dilute solution up to saturation).